Comparison of the Effectiveness of Administration of Nusantara Medicinal Plants on the Incident of Flour Albus for Teenage Women in 2024 - Yuliwati, Nanik; Safitri, Eka Nur; Aulia, Nuri; Nurjanah, Siti; Utami, Sri Mega (Jurnal Penelitian Pendidikan IPA, 2024)
A common reproductive health issue among Indonesian teenagers is vaginal discharge (Flour albus), with 75% of the 37.4 million adolescent population affected in 2023. Vaginal discharge, or leukorrhea, is the production of pus-like mucus. While normal discharge helps keep the vagina clean, abnormal discharge can signal health issues. This quantitative study used a quasi-experimental two-group pre-test post-test design, involving 80 young women with vaginal discharge over seven days, divided into eight groups. Treatments included pineapple juice, boiled betel leaves, turmeric, red rose tea, bay leaves, soursop leaves, binahong leaves, and aloe vera. Statistical analysis with Anova-One Way (Sig. < 0.05) showed significant effects of the interventions. Tukey's test revealed boiled betel leaf had the highest average reduction (mean 2.30), while aloe vera had the lowest (mean 5.70), suggesting medicinal plants are effective in treating vaginal discharge among adolescent girls in Lampung and Karawang Regencies.